Interpersonal communication between teachers and students in pancasila education learning - Lisnawati Rusmin; Safitri Joko (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to evaluate the effectiveness of interpersonal communication between teachers and students in the Pancasila Education learning process, specifically in grades IV and VI. The research also identifies the factors that hinder effective communication in the classroom, including barriers to message delivery and student engagement. Interpersonal communication is crucial in the learning process as it influences student understanding and participation, especially in moral and civic education subjects such as Pancasila Education. The research utilizes a qualitative approach with descriptive methodology, focusing on data gathered through observations, interviews, and documentation. A purposive sampling method was employed to select key informants, including teachers and students from the Pancasila Education classes. Data analysis followed the steps of data collection, reduction, display, and conclusion drawing. The findings indicate that while interpersonal communication between teachers and students is generally effective, challenges persist, such as the lack of learning media and excessive verbal or emotional messages from teachers that hinder student participation. These communication barriers contribute to misunderstandings and decreased student engagement during lessons. Based on these findings, the study recommends that teachers enhance their communication strategies by incorporating visual aids and reducing overly emotional or complex verbal communication. Furthermore, fostering a more interactive and inclusive classroom environment could help improve students' comprehension and active involvement in Pancasila Education.